Wheat Encodes Small, Secreted Proteins That Contribute to Resistance to Septoria Tritici Blotch - Zhou, Binbin; Benbow, Harriet R.; Brennan, Ciarán J.; Arunachalam, Chanemougasoundharam; Karki, Sujit J.; Mullins, Ewen; Feechan, Angela; Burke, James I.; Doohan, Fiona M. (Frontiers in Genetics, 2020)
During plant–pathogen interactions, pathogens secrete many rapidly evolving, small secreted proteins (SSPs) that can modify plant defense and permit pathogens to colonize plant tissue. The fungal pathogen Zymoseptoria tritici is the causal agent of Septoria tritici blotch (STB), one of the most important foliar diseases of wheat, globally. Z. tritici is a strictly apoplastic pathogen that can secrete numerous proteins into the apoplast of wheat leaves to promote infection. We sought to determine if, during STB infection, wheat also secretes small proteins into the apoplast to mediate the recognition of pathogen proteins and/or induce defense responses. To explore this, we developed an SSP-discovery pipeline to identify small, secreted proteins from wheat genomic data. Using this pipeline, we identified 6,998 SSPs, representing 2.3% of all proteins encoded by the wheat genome. We then mined a microarray dataset, detailing a resistant and susceptible host response to STB, and identified 141 Z. tritici- responsive SSPs, representing 4.7% of all proteins encoded by Z. tritici – responsive genes. We demonstrate that a subset of these SSPs have a functional signal peptide and can interact with Z. tritici SSPs. Transiently silencing two of these wheat SSPs using virus-induced gene silencing (VIGS) shows an increase in susceptibility to STB, confirming their role in defense against Z. tritici.